Diagnostic performance of MRI for staging peritoneal metastases in patients with colorectal cancer after neoadjuvant chemotherapy. Issue 149 (April 2022) - Rijsemus, C.J.V.; Kok, N.F.M.; Aalbers, A.G.J.; Buffart, T.E.; Fijneman, R.J.A.; Snaebjornsson, P.; Engbersen, M.P.; Lambregts, D.M.J.; Beets-Tan, R.G.H.; Lahaye, M.J.
Abstract: Introduction: MRI improves the selection of patients with colorectal cancer (CRC) and peritoneal metastases (PM) for cytoreductive surgery by accurately assessing the extent of PM reflected as the peritoneal cancer index (PCI). The performance of MRI after neoadjuvant chemotherapy (NACT) for staging PM, however is unknown. The purpose of this study was to determine whether MRI could also accurately determine the PCI after NACT. Materials and Methods: This was a single-centre, retrospective study of patients with PM from CRC or appendiceal origin who received NACT followed by diffusion-weighted (DW)-MRI and surgery from January 2016 to February 2021. Two radiologists assessed the PCI on restaging DW-MRI (mriPCI). The reference standard was the surgical PCI (sPCI). The main outcome was the diagnostic performance of restaging DW-MRI in predicting whether patients were eligible for cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC), defined as a PCI < 21 with metastases on resectable locations. If CRS-HIPEC was performed, the resected peritoneal lesions were assessed and correlated with the final pathological PCI (pPCI). Results: Thirty-three patients were included. Both readers correctly detected all 23 patients with resectable disease. Eight out of ten patients with unresectable disease during staging surgery were detected by both readers with MRI. The intraclass correlation (ICC) between both readers was excellent (0⋅87 (95% CI: 0⋅75 to 0⋅93)). The ICC between pPCI and mriPCI was 0⋅74 (0⋅49-0⋅88) and 0⋅82 (0⋅66-0⋅91) for the 2 readers. Surgical PCI (sPCI) had a similar correlation as mriPCI with pPCI 0⋅82 (0⋅62- 0⋅92)) and 0⋅81 (0⋅57-0⋅92)). Conclusion: DW-MRI is a promising tool to reassess the peritoneal cancer index after neoadjuvant chemotherapy.